Transcatheter closure of ruptured sinus of Valsalva aneurysm into the right ventricle with an Amplatzer Vascular Plug II - Rittger, Harald; Gundlach, Ulrike; Koch, Andreas (Catheterization and Cardiovascular Interventions, 2015)
We report a case of a 52-year-old female patient with perforated sinus of Valsalva (SVA) aneurysm presenting with severe left-to-right shunt from the aorta into the right ventricle.Aneuryms of the aortic sinus, better known as SVA are rare. Until interventional devices were introduced, the only treatment option for ruptured SVA aneurysms was surgery.The case was discussed in the heart team and decision was made to implant an Amplatzer Vascular Plug (AVP) II. Initially, closing attempts using AVP 16 mm and 14 mm devices were performed. Presumably as a consequence of inadequate sizing, the discs were not well formed in the connecting tunnel, leaving a severe rest shunt after both procedures. Finally, after implantation of a 12 mm AVP-device, only a minimal rest shunt remained detectable. Absence of aortic regurgitation was confirmed by transesophageal echocardiography, and the occluder was released. Mean pulmonary artery pressure immediately decreased from 39 to 15 mm Hg. Medication with aspirin (100 mg qid) and clopidogrel (75 mg qid) was initiated. Follow-up examinations at 4 weeks and 3 months confirmed the minimal rest shunt and a continuous decrease of systolic pulmonary artery pressure to 35 mm Hg, as assessed with transthoracal echocardiography.In conclusion, in cases of SVA rupture, closure with an AVP II represents an alternative to surgical treatment and other devices used for transcatheter treatment of SVA. © 2014 Wiley Periodicals, Inc.
EVALuna2:12010